2014
DOI: 10.3892/ijmm.2014.1745
|View full text |Cite
|
Sign up to set email alerts
|

The green tea extract epigallocatechin-3-gallate inhibits irradiation-induced pulmonary fibrosis in adult rats

Abstract: The present study evaluated the effect of epigallocatechin-3-gallate (EGCG), the most abundant catechin in green tea, on irradiation-induced pulmonary fibrosis and elucidated its mechanism of action. A rat model of irradiation-induced pulmonary fibrosis was generated using a 60Co irradiator and a dose of 22 Gy. Rats were intraperitoneally injected with EGCG (25 mg/kg) or dexamethasone (DEX; 5 mg/kg) daily for 30 days. Mortality rates and lung index values were calculated. The severity of fibrosis was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…Subsequently, Nrf-2 is dissociated, stabilized and translocated into the nucleus [20]. As a cell survival signaling, the activation of Nrf-2 will accelerate the production of endogenous antioxidant enzymes (including HO-1, CAT and SOD) via binding to the antioxidant response element in the promoter regions of these genes, and subsequently inducing their transcriptions [25]. Furthermore, HO-1 possessed both anti-inflammatory and anti-oxidative properties in response to oxidative stress [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Nrf-2 is dissociated, stabilized and translocated into the nucleus [20]. As a cell survival signaling, the activation of Nrf-2 will accelerate the production of endogenous antioxidant enzymes (including HO-1, CAT and SOD) via binding to the antioxidant response element in the promoter regions of these genes, and subsequently inducing their transcriptions [25]. Furthermore, HO-1 possessed both anti-inflammatory and anti-oxidative properties in response to oxidative stress [24].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 is a powerful pro-fibrogenic cytokine. It modulates the phenotype, proliferation and functions of fibroblasts, promotes the transdifferentiation of myofibroblasts, as well as induces the deposition of ECM [23, 25]. TGF-β superfamily elicit signaling through distinctly combining to their transmembrane receptors (TGF-βRI and II) [30].…”
Section: Discussionmentioning
confidence: 99%
“…TBARS levels most likely 292 determine the degree of organic lipid peroxidation, which denotes 293 the severity of cell membranes damage [41]. Chronic oral 294 administration of GA could increase the GPx activity which 295…”
mentioning
confidence: 99%
“…response [41]. The protective effect of GA was also found for total 298 thiol which was applied for evaluation the non-enzymatic defense 299 potential of the cells against the oxidative stress [38].…”
mentioning
confidence: 99%
“…RPF, considered a result of chronic lung damage, occurs at 6–24 months post‐radiotherapy, and includes irreversible corruption of the alveoli, activation of myofibroblasts, abnormal deposition of extracellular collagen matrix, and deregulated remodeling of lung tissue . Clinical data have demonstrated that the incidence of RILI ranges from 20.3% to 36.9% . However, only a few successful therapeutic strategies have been proposed, despite extensive research.…”
Section: Introductionmentioning
confidence: 99%